Improvements to the procedure for determination of the residual lifetime of railway vehicles (Transport systems and technologies, 2023)
Existing research concerning the extention of the service life of various types of railway vehicles and assessing its remaining lifetime has been reviewed and analyzed. It has been established that the vast majority of studies relate to the assessment of the residual lifetime of various types of railway rolling stock based on the results of technical diagnostics and routine tests, as well as the assessment of corrosion wear of supporting elements and vehicles bodies. At the same time, little attention has been paid to the issue of improving existing programs and procedures of complex technical diagnostics. It was determined that the set of diagnostics operations for the extension of the service life includes routine tests of a test sample and examination of the technical condition of the metal structure of each railway vehicle for mechanical and corrosive damage.It is proposed to make changes to the existing current programs and procedures in such key sections as: terminology, objects of technical diagnostics and tests, selection of a test sample for routine tests, execution order and methods of technical diagnostics and routine tests, data processing and evaluation of results. A comprehensive approach for assessing the residual lifetime of railway vehicles is also proposed.
Keywords: railway vehicles, residual lifetime, routine tests, rolling stock, technical diagnostics.